The Transfer of Intellectual Property Rights as Object of Fiduciary Guarantee - Anis Mashdurohatun; Gunarto Gunarto; Adhi Budi Susilo (Jurnal Akta, 2022)
The transfer in Intellectual Property Rights (IPR) "can be transferred or transferred" only economic rights. The transfer must be made clearly and in writing either with or without a notarial deed so that the transfer must be based on an agreement. This study aims to examine and analyze the transfer of intellectual property rights in the property law system, and to analyze the transfer of intellectual property rights as objects of fiduciary guarantees. The approach in this study is to use a socio-legal approach. This type of research is a qualitative research. The types of data used are primary and secondary data. Techniques for collecting data, through literature and field studies. Data collection through field studies is through observation and interviews. Observation is research that is conducted directly on the object under study by conducting interviews with research resource persons. The data analysis used is qualitatively inductive. The results of the study found that intellectual property rights as object law in Article 499 and Article 507 of the Civil Code so that intellectual property rights are transferred as objects of fiduciary guarantees through agreements, in accordance with the main agreement. Furthermore, the transfer of IPR as a fiduciary guarantee, of course, underlies the transfer of property rights in accordance with the provisions of the Civil Code, the law on intellectual property rights and the law on fiduciary guarantees, which have been stated in the agreement clause authentically.